The Effects of Vibrations Experienced during Road vs. Off-road Cycling - Macdermid, P. W.; Fink, P. W.; Stannard, S. R. (International Journal of Sports Medicine, 2015)
The purpose of this investigation was to compare the effects of vibrations experienced during off-road and road cycling. It was hypothesised that additional damping will be expressed through a greater work demand and increased physiological markers when travelling at the same speed over an identical terrain profile. Participants ascended a tar-sealed road climb and a single-track off-road climb at a predetermined speed. Time, speed, power, cadence, heart rate and V̇ O2 were sampled and logged every second while tri-axial accelerometers recorded accelerations (128 Hz) to quantify vibrations experienced. Statistical analysis indicated accelerations to be greater during the off-road condition (p<0.0001) with post-hoc analysis exposing differences (p<0.001) for handlebar, arm, leg and seat post but not the lower back or head. The increased accelerations during off-road riding are associated with the increased vibrations and rolling resistance experienced. This led to increases in the work done (road: 280±69 vs. off-road: 312±74 W, p=0.0003) and, consequentially, a significant increase in the physiological markers V̇ O2 (road: 48.5±7.5 off-road 51.4±7.3 ml·kg−1·min−1, p=0.0033) and heart rate (road: 161±10 off-road 170±10 bpm, p=0.0001) during the off-road condition. Such physiological differences and their causes are important to understand in order to provide suitable training recommendations or technological interventions for improving competitive performance or recreational enjoyment.
Keywords: mountain biking; accelerometers; rolling resistance; cycling economy; performance